PENGENALAN SIMBOL LINGKUNGAN DAN KESEHATAN DI SDN 1 POMAHAN KECAMATAN PULUNG KABUPATEN PONOROGO (Jurnal Abdikarya: Jurnal Karya Pengabdian Dosen Dan Mahasiswa, 2019)
The school is the best place to introduce children to useful knowledge where they will later become adults. Therefore schools, especially education at the elementary level need to be supported and facilitated as well as possible so as to facilitate students in learning.SDN 1 Pomahan in the Krajan Hamlet stands on a very large area. However, we observed that there were still very few facilities provided for both external and internal activities of students in learning and knowing knowledge.Related externally, which includes the school environment. We see that there is still a lack of symbolic information that should be more available to be presented and introduced to students. Symbols such as preserving the environment, and how to maintain health are very important to be introduced early. Especially children of their age, like to play together but incidentally they rarely care about the environment when it's cool. As well as maintaining health after playing, most children of their age do not yet know the steps to clean good and right hands and so on.